Profile of rural tourism consumers in Serbia and Austria - Tomić, Slavica; Leković, Ksenija; Eskerod, Pernille; Zedlacher, Eva (Anali Ekonomskog fakulteta u Subotici, 2020)
In order to achieve successful positioning, rural tourism managers and marketers need to understand consumer behaviour. Above all, they need to answer the question of which customer profiles are suitable to particular tourist destinations There are three types of statistical measurement used for research into consumer, i.e. tourist behaviour, and those are volume, value and profile. A profile encompasses characteristics of the consumers per se and characteristics of trae. The aim of the paper is to define the profile of rural tourism consumer based on the results of the conducted research, taking into account two socio-demographic characteristics of the consumers – age and education level in relation to three characteristics of travel – frequency of engaging in rural tourism, travel companions and information sources used to plan the trip. The research encompassed 150 respondents each from Serbia and Austria respectively. Cross-tabulation method was used for testing the set hypotheses.